2015
DOI: 10.1017/s1355617715000909
|View full text |Cite
|
Sign up to set email alerts
|

Processing of Facial Emotion in Bipolar Depression and Euthymia

Abstract: Previous studies of facial emotion processing in bipolar disorder (BD) have reported conflicting findings. In independently conducted studies, we investigate facial emotion labeling in euthymic and depressed BD patients using tasks with static and dynamically morphed images of different emotions displayed at different intensities. Study 1 included 38 euthymic BD patients and 28 controls. Participants completed two tasks: labeling of static images of basic facial emotions (anger, disgust, fear, happy, sad) show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 53 publications
3
21
0
1
Order By: Relevance
“…As in our study, the effect size was large for most measures. In accordance with other results, several studies , but not all , have found emotion recognition deficits in EBP. Three recent meta‐analysis have confirmed a small but significant effect size (Cohen′s d < 0.5) for facial emotion recognition, similar to that observed in our study for the perceiving emotions branch.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…As in our study, the effect size was large for most measures. In accordance with other results, several studies , but not all , have found emotion recognition deficits in EBP. Three recent meta‐analysis have confirmed a small but significant effect size (Cohen′s d < 0.5) for facial emotion recognition, similar to that observed in our study for the perceiving emotions branch.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have shown that patients with BD have emotion processing deficits not only during acute exacerbations of their illness, but also during periods of euthymia although not all studies could replicate those findings . In a recent meta‐analysis, no significant differences were observed between patients with BD and controls for facial affect recognition.…”
Section: Introductionmentioning
confidence: 97%
“…Impairments in social cognition have also been reported in both MDD and BPD, specifically for facial emotional identification and differentiation, as reported in a meta-analysis (Kohler et al, 2011). Studies of the extent to which these measures reflect current state versus trait (Robinson et al, 2015; Van Rheenen and Rossell, 2014) or severity (Munkler et al, 2015) have been inconsistent. Among patients with depression, a recent meta-analysis showed impaired recognition of emotion for angry, disgusted, fearful, happy and surprised faces, but not sad faces (Dalili et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…
In their recent study investigating emotion recognition impairments in bipolar disorder (BD), Robinson et al (2015) report that two well-characterized groups of BD individuals failed to show performance deficits on a series of facial emotion processing tasks when compared to controls. This is in contrast to our findings of BD patient impairments on a similar set of facial emotion recognition measures in a group of stable outpatients in mixed mood states but with relatively minimal mean symptom severity .

Robinson et al state that methodological issues related to neurocognitive ability may account for some inconsistencies in the literature.

…”
mentioning
confidence: 99%